Discretion of Power of the Indonesian National Police Impacts the Abuse of Power in the Case of Letter Forgery of Red Notice "Fugitive Djoko Tjandra" - Riyadi, Bambang Slamet; Hermanto, Asep Bambang; Harlina, Indah; Purnomo, Hadi (International Journal of Criminology and Sociology, 2022)
This research was a case study presenting a red notice that was suspected of being false against fugitive Djoko Tjandra by two police generals at the State Police of the Republic of Indonesia. This was a case study research and the research approach method was qualitative. Creswell defines the qualitative method as a research method based on a constructive perspective, that is various meanings; meanings that are constructed socially and historically to develop a theory or pattern. The researchers collected and developed open data, intending to develop themes from the data obtained. The results of the study, based on the exposure to the case analysis, it is suspected that there has been an abuse of power against the power and authority of the state institution of the Indonesian National Police. The researchers suggested that it is better if the legislators of the laws and regulations of the Police of the Republic of Indonesia think about it whether operational accountability is appropriate to the executive of the President of the Republic of Indonesia. Therefore, there is a check and balance of law enforcement behavior carried out by the police.